1973
DOI: 10.1159/000208363
|View full text |Cite
|
Sign up to set email alerts
|

Blood Group and Tissue Mosaicism in a Natal Indian Woman

Abstract: A normal 46, XX karyotype was demonstrated in an Indian woman who has 2 approximately equal populations of red cells and of leucocytes. She also has skin mosaicism. She is a normal female and has borne 4 healthy children. The ABO, Ss, Rh and Fy groups of her 2 red cell populations differed, but both were Le(a+b-) although she is a secretor of B and H substances. The relationship between this and the 7 examples of dispermywith blood group mosaicism reported in the literature is discussed briefly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…This theory of intracellular interaction was sup ported by the secretions observed in Mrs. T.R., the first Durban chimera [48], Both Mr. D.W. and Mrs. T.R. were Le(a + b-) but secretors of ABH, a surprising …”
Section: Contributions Of Dispermie Chimeras Understanding Of Lewis Amentioning
confidence: 93%
“…This theory of intracellular interaction was sup ported by the secretions observed in Mrs. T.R., the first Durban chimera [48], Both Mr. D.W. and Mrs. T.R. were Le(a + b-) but secretors of ABH, a surprising …”
Section: Contributions Of Dispermie Chimeras Understanding Of Lewis Amentioning
confidence: 93%
“…A more detailed investigation of the distribution of the light-and dark-brown skin pigmentation in Mrs T.R. than had been possible in the first study (Moores, 1973) was reported by Findlay and Moores in 1980. Fundamentally, Mrs T.R.…”
Section: Skin Pigmentationmentioning
confidence: 88%
“…A fresh blood sample from Mrs T.R. 's mother, 1-2, was found to be Le(a+b-), showing that the Le(a-) result recorded earlier (Moores, 1973) had been incorrect. However, fortunately , this made no difference to the interpretation of the inheritance in the family.…”
Section: Family Pedigreementioning
confidence: 89%
See 1 more Smart Citation
“…The sepa rate genetic origins of their cell lines distinguish chimaer as from mosaics who characteristically originate from a single zygote [2]. The literature contains counts of XX/XY hermaphrodite but few of XX/XX female disper mie chimaeras [1], The first 2 females with double pop ulations of red cells recorded were both from Natal [1,[3][4][5], Mayr et al [6] reported the 3rd female but two populations of red cells were not observed in her blood.…”
mentioning
confidence: 99%